Relative abundances of dinoflagellate cysts in surface sediments from Young Sound fjord, North-East Greenland - Meri Marianne Mäkelä; Tiia Luostarinen; Sofia Ribeiro; Kaarina Weckström; Mikael K Sejr; Mie Hylstofte Sichlau Winding; Maija Heikkilä (PANGAEA, 2025)
Surface sediment samples collected from Young Sound fjord, Northeast Greenland, in 2013 or 2015. The surface sediment cores were collected as individual trips from small rubber boats using a Rumohr lot corer, multi corer or Kayak corer. Sediment samples were analysed for relative abundances of dinoflagellate cysts using a Zeiss Axio Imager.A2 upright research microscope with 60x oil immersion objective and a total magnification of exttimes600.
In: Mäkelä, MM et al. (2025): Diatom and dinoflagellate cysts determination from Young Sound fjord, North-East Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982994